Impact of managerial overconfidence and government intervention on firm leverage decision: A MARS model approach - Ting I.W.K.; Lean H.H.; Kweh Q.L.; Azizan N.A. (Faculty of Economics and Administration, 2023)
This paper investigates the impact of managerial overconfidence and government intervention on a firms leverage decision. The Motivation, Ability, Roles and Situation Factors (MARS) model is employed to examine its impact on leverage decision. Dynamic panel models are applied to examine the relationship between managerial overconfidence, government intervention and leverage decision of publicly listed companies in Malaysia for the period 2004-2013. The findings are as follows. (1) When CEOs are motivated, their overconfidence is significantly and positively related to debt; (2) The CEOs ability is significantly and positively related to leverage decision; (3) The CEOs role is significantly and negatively related to leverage decision. (4) Government ownership moderates the relationship between managerial overconfidence and firm leverage decision. (5) Malaysian public listed firms adjust debt towards an optimal level and the speed of adjustment is approximately 21% to 26% per annum. The findings also pave the way for further study of antecedent conditions in predicting the extent of firm leverage decision from the behavioural perspective. 2016, Faculty of Economics and Administration. All rights reserved.